â€œThe Effect of Sharia Banking Financing and Non-Sharia Banking Financing on the GRDP in Indonesiaâ€ - B01112027, Firmansyah B01112027 (Jurnal Pembangunan dan Pemerataan, 2016)
This thesis is entitled â€œthe Effect of Sharia Banking Financing and Non-Sharia Banking Financing on the GRDP in Indonesiaâ€. The research aims 1) to analyze the effect of Sharia banking financing on GRDP in Indonesia, 2) To analyze the effect of non-Sharia banking financing on GRDP in Indonesia. The method used in this research was a panel regression which is a combination of time series data (between time) and cross section data (between individuals or space), and processed by a computer using a program of software economics views (e-views). The method used was the fixed effect model. The conclusions of the research were Sharia banking financing had a significant effect on the GRDP because of the growth of Sharia banking financing, high demand of the society, and the Muslim majority of Indonesia people. Non-Sharia Banking Financing had a significant effect on GRDP because it is increasing due to the increase of fund distribution in accordance with peopleâ€™s demand to fulfill the needs and increase business capital Keyword: GRDP, Sharia banking financing, Non-Sharia banking financing.